Community-acquired pneumonia and Gram-negative bacilli in Cambodia—incidence, risk factors and clinical characteristics. (22nd March 2018) - Inghammar, Malin; Borand, Laurence; Goyet, Sophie; Rammaert, Blandine; Te, Vantha; Lorn Try, Patrich; Guillard, Bertrand; Buchy, Philippe; Vong, Sirenda; Tek Chheng, Eap; Cavailler, Philippe; Mayaud, Charles; et al.
Abstract: Background: In Western settings, community-acquired pneumonia (CAP) due to Gram-negative bacilli (GNB) is relatively rare. Previous studies from Asia, however, indicate a higher prevalence of GNB in CAP, but data, particularly from Southeast Asia, are limited. Methods: This is a prospective observational study of 1451 patients ≥15 y of age with CAP from two hospitals in Cambodia between 2007 and 2010. The proportion of GNB was estimated. Risk factors and clinical characteristics of CAP due to GNB were assessed using logistic regression models. Results: The prevalence of GNB was 8.6% in all CAP patients and 15.8% among those with a valid respiratory sample. GNB infection was independently associated with diabetes, higher leucocyte count and CAP severity. Mortality was higher in patients with CAP due to GNB. Conclusions: We found a high proportion of GNB in a population hospitalized for CAP in Cambodia. Given the complex antimicrobial sensitivity patterns of certain GNBs and the rapid emergence of multidrug-resistant GNB, microbiological laboratory capacity should be strengthened and prospective clinical trials comparing empiric treatment algorithms according to the severity of CAP are needed.